Extraction of cellulose nano-whiskers using ionic liquid-assisted ultra-sonication: optimization and mathematical modelling using Box–Behnken design - Chowdhury, Zaira Zaman; Chandran, R. Reevenishaa Ravi; Jahan, Afrin; Khalid, Khalisanni; Rahman, Md. Mahfujur; Al-Amin, Md; Pivehzhani, Omid Akbarzadeh; Badruddin, Irfan Anjum; Khan, T. M. Yunus; Kamangar, Sarfaraz; Hamizi, Nor Aliya; Abdul Wahab, Yasmin; et al. (MDPI, 2019)
This study focuses on the extraction of cellulose nano-whiskers (CNWs) from the leaves of Adansonia kilima (AK), usually known as African baobab, using a combination of a microwave-assisted alkali (KOH) pre-treatment with subsequent bleaching process prior to ultra-sonication. Ultra-sonication was carried out using the ionic liquid (IL) 1-butyl-3-methylimidazolium hydrogen sulfate (Bmim-HSO4). Process parameters for ultra-sonication were optimized using a two-level factorial Box–Behnken design (BBD). Process variables such as ultra-sonication power (x1), hydrolysing time (x2) and temperature (x3) were varied. Responses selected were percentage crystallinity index, CrI% (y1) and yield% (y1) for the finally procured CNWs sample. Regression analysis was carried out to develop quadratic model to analyze the effect of process variables on IL-assisted ultra-sonication process. Analysis of variance (ANOVA) showed that ultra-sonication power was the most influential aspect for hydrolyzing the amorphous segments of crude cellulose extracted from baobab leaves. A relative study of the physio-chemical properties of the starting lignocellulosic substrate (AK), KOH pre-treated, bleached and IL-assisted ultra-sonicated CNWs was conducted. The synthesized samples were characterized using Fourier transform infrared spectroscopy, Scanning electron microscopy, atomic force microscopy, high resolution transmission electron microscopy, X-ray diffraction and thermo-gravimetric and zeta potential analysis. Under optimum condition, the extracted CNWs showed an average width of 15–20 nm; with high crystallinity index of 86.46%. This research provides an insight about the delignification of Adansonia kilima (AK) leaves and its effective conversion to CNWs having high crystallinity.